Russian-Language Poetry in Ukraine: Specificity, Authors and Modern Challenges - Sventsitskaya, Elina (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2023)
The object of this article is modern Russian-language poetry in Ukraine as represented by its main personalities. The author argues that Russian-language literature in Ukraine is afar from accidental phenomenon andthat it seeks to solve problems of creative self-expression in no way related to politics. It has never sought tosupport or glorify the authorities in Russia. Rather its goal has been the impartial analysis of the state of society. This paper examines the diversity of creative researchofthe poetry and its response to contemporary challenges. Tothis end the meaning and boundaries of“Russian-language literature of Ukraine “ are clariﬁed and shown to be determined by its connection to two East Slavic cultures at once and the integration of two mentalities in one author, which, naturally, is reﬂected in the poetics of their works. The work of the most famous contemporary poets is examined as to the diversity of their creative searches. The choice of poets is the importance given to the multi-directionality of their searches, as well as the representativeness of their work aspart ofthe literary process in Ukraine, i. e., its non-randomness in this context and its aesthetic qualities. The article not only demonstrates what Russian-language poetry of Ukraine is at the present stage, but also highlights the transformations it is undergoing in response to wartime challenges.